Arrest and Trait Aggression Correlates of Emergency Department Use. (July 2019) - Erlyana, Erlyana; Reynolds, Grace L.; Fisher, Dennis G.; Pedersen, William C.; Van Otterloo, Lucy
This study examined the associations between arrest and incarceration, trait aggression, and emergency department (ED) use. Data were collected from 525 clients who visited the Center for Behavioral Research and Services in Long Beach, CA, using the following instruments: Risk Behavior Assessment, Risk Behavior Follow-Up Assessment, the Aggression Questionnaire (AQ), the Displaced AQ, and the parole and Legal Status section of the Addiction Severity Index. The bivariate analysis suggested that ED use was significantly associated with trait aggression and trait-displaced aggression among those with a history of incarceration. In the logistic regression, weapons offenses, manslaughter/homicide, being male, and being Black were significantly associated with ED use. Identification and management of aggressive trait personality are important in improving the management of postrelease care in transition to clinical networks and community-based health care settings.